Role of PKR in the Inhibition of Proliferation and Translation by Polycystin-1. (23rd June 2019) - Tang, Yan; Shi, Guang; Yang, JungWoo; Zheng, Wang; Tang, Jingfeng; Chen, Xing-Zhen; Yang, Jianzheng; Wang, Zuocheng
Abstract : Autosomal dominant polycystic kidney disease (ADPKD) is mainly caused by mutations in the PKD1 ( 85%) or PKD2 ( 15%) gene which, respectively, encode polycystin-1 (PC1) and polycystin-2 (PC2). How PC1 regulates cell proliferation and apoptosis has been studied for decades but the underlying mechanisms remain controversial. Protein kinase RNA-activated (PKR) is activated by interferons or double-stranded RNAs, inhibits protein translation, and induces cell apoptosis. In a previous study, we found that PC1 reduces apoptosis through suppressing the PKR/eIF2 α signaling. Whether and how PKR is involved in PC1-inhibited proliferation and protein synthesis remains unknown. Here we found that knockdown of PKR abolishes PC1-inhibited proliferation and translation. Because suppressed PKR-eIF2 α signaling/activity by PC1 would stimulate, rather than inhibit, the proliferation and translation, we examined the effect of dominant negative PKR mutant K296R that has no kinase activity and found that it enhances the inhibition of proliferation and translation by PC1. Thus, our study showed that inhibition of cell proliferation and protein synthesis by PC1 is mediated by the total expression but not the kinase activity of PKR, possibly through physical association.